2017
DOI: 10.2147/ijgm.s136921
|View full text |Cite
|
Sign up to set email alerts
|

Association of code status discussion with invasive procedures among advanced-stage cancer and noncancer patients

Abstract: BackgroundCode status discussion is associated with a decrease in invasive procedures among terminally ill cancer patients. We investigated the association between code status discussion on admission and incidence of invasive procedures, cardiopulmonary resuscitation (CPR), and opioid use among inpatients with advanced stages of cancer and noncancer diseases.MethodsWe performed a retrospective cohort study in a single center, Ito Municipal Hospital, Japan. Participants were patients who were admitted to the De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…10 In Japan, more than 70% of hospitalized patients are aged ≥ 65 years, approximately three in four die in the hospital, and two in ten do not have DNR orders. 11 In this context, we used a large population-based database from 81 Japanese hospitals to investigate the survival rate after CPR among hospitalized elderly patients and to identify predictors associated with survival.…”
Section: Introductionmentioning
confidence: 99%
“…10 In Japan, more than 70% of hospitalized patients are aged ≥ 65 years, approximately three in four die in the hospital, and two in ten do not have DNR orders. 11 In this context, we used a large population-based database from 81 Japanese hospitals to investigate the survival rate after CPR among hospitalized elderly patients and to identify predictors associated with survival.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, discussing code status on admission reportedly decreased invasive procedures before death that cancer 25 and non-cancer inpatients in an advanced stage would like to avoid. 26 On admission is not an optimal time to initiate advance care planning; however, we should start advance care planning including code status discussion as soon as possible after admission.…”
Section: Discussionmentioning
confidence: 99%
“… 26 It has been reported that DNR discussion occurred less frequently for patients with a noncancer primary diagnosis, including HF, compared with cancer patients. 27 , 28 In cases of chronic HF, patients’ health status declines slowly with occasional acute exacerbation, from which they often recover. 29 , 30 By contrast, patients in the advanced stage of cancer have a more predictable progressive downward trajectory with clear prognosis.…”
Section: Discussionmentioning
confidence: 99%
“… 36 , 37 End-of-life discussion was associated with a decrease in unnecessary invasive procedures, including central venous catheter placement, intubation with mechanical ventilation, CPR, and increase of opioid use during the advanced stage of illnesses, including HF. 27 Physicians should not delay the initiation of end-of-life discussions with patients with HF to provide better quality of end of life.…”
Section: Discussionmentioning
confidence: 99%